2021
DOI: 10.1177/0011392120985874
|View full text |Cite
|
Sign up to set email alerts
|

‘Save the children!’: Governing left-behind children through family in China’s Great Migration

Abstract: Existing scholarship on the lives and wellbeing of China’s left-behind children often frames the issues as a function of their parents’ migration, which leaves a significant gap in discussing the role of the state in shaping the institutional framework that these families operate within, cope or struggle with. Through critically interrogating public discourses based on articles from a mainstream newspaper and policy documents since the early 2000s, this article situates a sociological inquiry into the discursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 45 publications
(55 reference statements)
0
19
0
Order By: Relevance
“…Similar findings were found by Fellmeth et al ( 2018 ) who stated that studies have shown that individuals with high social support tend to have higher levels of self-esteem. In addition, according to Gu ( 2021 ), perceived social support is closely related to self-esteem. Social support is a crucial factor that enhances the self-esteem of the LB children.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar findings were found by Fellmeth et al ( 2018 ) who stated that studies have shown that individuals with high social support tend to have higher levels of self-esteem. In addition, according to Gu ( 2021 ), perceived social support is closely related to self-esteem. Social support is a crucial factor that enhances the self-esteem of the LB children.…”
Section: Discussionmentioning
confidence: 99%
“…According to Gu ( 2021 ), perceived social support is closely related to self-esteem. Individuals having extremely low social support would have low satisfaction levels which would ultimately result in low self-esteem (Xin et al, 2019 ).…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations